Evaluation of the basic assay performance of the GeneSoc® rapid PCR testing system for detection of severe acute respiratory syndrome coronavirus 2. - Ryosuke Watanabe; Satomi Asai; Hidehumi Kakizoe; Hirofumi Saeki; Atsuko Masukawa; Miki Miyazawa; Kazumi Ohtagawa; Mend-Amar Ravzanaaadii; Mika Doi; Haruyo Atsumi; Kazuo Umezawa; Hayato Miyachi (PLoS ONE)
In the ongoing coronavirus disease 2019 (COVID-19) pandemic, PCR has been widely used for screening patients displaying relevant symptoms. The rapid detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enables prompt diagnosis and the implementation of proper precautionary and isolation measures for the patient. In the present study, we aimed to evaluate the basic assay performance of an innovative PCR system, GeneSoC® (Kyorin Pharmaceutical Co. Ltd., Tokyo, Japan). A total of 1,445 clinical samples were submitted to the clinical laboratory, including confirmed or suspected cases of COVID-19, from February 13 to August 31. Specimen types included nasopharyngeal swabs. The sampling was performed several times for each patient every 2-7 days. Using this system, sequences specific for SARS-CoV-2 RNA could be detected in a sample within 10-15 min using the microfluidic thermal cycling technology. Analytical sensitivity studies showed that GeneSoC® could detect the target sequence of the viral envelope and RNA-dependent RNA-polymerase (RdRp) genes at 5 and 10 copies/μL, respectively. The precision of the GeneSoC® measurements using clinical isolates of the virus at a concentration of 103 copies/μL was favorable for both the genes; within-run repeatability and between-run reproducibility coefficient of variation values were less than 3% and 2%, respectively; and the reproducibility of inter-detection units was less than 5%. Method comparison by LightCycler® 480 showed the positive and negative agreement to be 100% [(174/174) and (1271/1271), respectively]. GeneSoC® proved to be a rapid and reliable detection system for the prompt diagnosis of symptomatic COVID-19 patients and could help reduce the spread of infections and facilitate more rapid treatment of infected patients.